Stabilization of Brain Mast Cells Alleviates LPS-Induced Neuroinflammation by Inhibiting Microglia Activation - Dong, Hongquan; Wang, Yiming; Zhang, Xiaojun; Zhang, Xiang; Qian, Yanning; Ding, Haixia; Zhang, Shu (Frontiers in Cellular Neuroscience, 2019)
Background The functional aspects of mast cell-microglia interactions are important in neuroinflammation. We have previously found that mast cell degranulation could directly induce microglia activation. However, the role of mast cell in LPS-induced microglia activation, neuroinflammation and cognitive impairment has not been clarified. Methods We studied brain microglia and mast cells interaction by site-directed injection of cromolyn in rat right hypothalamus using stereotaxic techniques. TFC and Y maze were used to assess cognitive function. Mast cells were stained by toluidine blue and calculated with Cell D software. Microglia activation was assessed by Iba1 immunohistochemistry. Conditioned medium from activated P815 cells induces microglial activation. The levels of cytokines were measured with Milliplex kit. Cell signalling was analysed by Western blotting. Results We find that “Mast cell stabilizer” cromolyn can ameliorate LPS-induced mast cells degranulation and cognitive dysfunction, and stabilization of mast cell is able to inhibit LPS-induced microglia activation, inflammatory factors release and MAPK, AKT and NF-κB signaling pathway activation in vivo and in vitro. Further LPS IP injection for 24 h induces significant microglia activation in the hypothalamus of the WT mice but has little effect on the microglia activation in KitW-sh/W-sh mice. We also find that LPS selectively provokes upregulation of expressions of H1R, H4R, PAR2, and TLR4, but deregulation of H2R and H3R expressions in the ipsilateral hypothalamus microglia, which was partially inhibits by cromolyn. Conclusions Taken together, our study provides evidence that stabilization of mast cells can inhibit LPS-induced neuroinflammation and memory impairment. Investigating the role of mast cell activation in neuroinflammation is an emerging new area to understand and effectively treat neuroinflammation-related diseases.